Why "IT" Course in the Curriculum of Library and Information Science Education? - Kemparaju, T. D.; Nyainboga, Constantine M. (Journal of Information and Knowledge, 2001)
The author defines IT, its needs, benefits and components. Observes the shift in the information culture from the view of traditional information against the Electronic Information and readiness for the future in this era of information age. The article also tackles IT's role in Jibrary schools and thoroughly examines the use and importance of internet and why it must he emphasised at the Library School's curriculum.